THE INFLUENCE OF INTERCHANNEL CORRELATION OF THE DESIRED SIGNALS, BEING COMBINED, ON MULTICHANNEL DETECTORS PERFORMANCE, USING METHODS OF SELECTION BY MAXIMUM AND MINIMUM - V. G. Bartenev; G. V. Bartenev; V. K. Bityukov; V. E. Kutepov (Российский технологический журнал)
The comparative efficiency analysis of two ways of multiplexing based on minimum and maximum selection methods has been carried out. It has been shown that minimum selection method is less effective than the maximum one for independent channels. Minimum selection method approaches efficiency of the maximum selection one when considering interchannel desired signal correlation. However this consideration implies the efficiency decrease of maximum selection method, while improving the efficiency of minimum selection one.